2015
DOI: 10.3892/mmr.2015.4256
|View full text |Cite
|
Sign up to set email alerts
|

De-methylation of displacement loop of mitochondrial DNA is associated with increased mitochondrial copy number and nicotinamide adenine dinucleotide subunit 2 expression in colorectal cancer

Abstract: DNA methylation occurs in the displacement loop (D-loop) region of mammals; however, D-loop regions of certain tumor tissue types were found to be de‑methylated. Whether hypomethylation of the D‑loop region is involved in the regulation of the mitochondrial DNA (mtDNA) copy number and nicotinamide adenine dinucleotide subunit 2 (ND‑2) expressions in colorectal cancer has remained elusive. In the present study, the association between methylation status of the D‑loop region, mtDNA copy number and ND‑2 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 21 publications
4
64
0
Order By: Relevance
“…More recently, it has been shown that methylation of the Dloop in the mitochondrial genome is decreased in colorectal cancer tissues compared with non-cancerous tissues [97].…”
Section: Current Studies On Mitochondrial Epigenetics In Human Diseasesmentioning
confidence: 99%
“…More recently, it has been shown that methylation of the Dloop in the mitochondrial genome is decreased in colorectal cancer tissues compared with non-cancerous tissues [97].…”
Section: Current Studies On Mitochondrial Epigenetics In Human Diseasesmentioning
confidence: 99%
“…Such supporting evidence, as reviewed by us elsewhere 11 , includes the discovery of a) a mitochondria-targeted human DNA methyltransferase 1 transcript variant (mtDNMT1) 12 , b) the presence of both CpG and CpH (where H is A, T or C) methylation 8, 1215 and, importantly, c) correlations with diseases such as cancer 16 , Down syndrome 17 and diabetes 18 . Although several of these papers hint toward an effect of mtDNA methylation on mitochondrial gene expression 12, 16, 1820 , a direct causal link has yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al investigated 44 colorectal cancer tissues and found the ratio of the methylation in D-loop region in colorectal cancer tissues was less than that in the noncancerous tissues [32]. Gao et al found the similar results in 65 colorectal cancer patients [33]. Govatati et al investigated the D-loop region of CRC patients in south Indian origin and put forward that D-loop sequence alterations were inherent risk factor for CRCs [34].…”
Section: D-loopmentioning
confidence: 99%